A constituição do conceito de narcisismo na teoria freudiana (1895-1914) - Filla, Munique Gaio (2018)
The purpose of the present study is to look into Freud's path to the introduction of the concept of narcissism in his theory. We start with narcissism while concept of the libido theory, to just afterwards come through the current formulation, task split in four steps. First we go back to Freud's theory of seduction, your resignation and the theoretical consequences of such renunciation, in order to point the emergence of infantile sexuality and to justify the way which was described primarily by the psychoanalyst. Second, we approach deeper infantile sexuality, highlighting the notion of autoerotism, and the theoretical obstacles against the transition to adult sexuality after puberty, marked by the meeting with the object. On a third moment, we have tracked the beginning of narcissism mentions on Freud's work, and exposed the bond between that and the choice of a homosexual object. Lastly, we have explored the admission of narcissism as a regular and universal phase of libido's development, and your inclusion as a intermediate stage between autoerotism and object love, showing, therefore, how Freud got close to the edges that characterized the conceptual composition of narcissism.